Trends and Determinants of Dividend Policy: A Study of London Stock Exchange, FTSE 350 Index - Li, ZW (2012)
This paper aims to investigate the stability and dominant determinants of dividend policy for a total of 242 UK dividend-paying companies listed on London Stock Exchange during the sample period 2002-2011. Particularly, the study examines if managers of UK listed firms tend to smooth dividends by conducting Lintner’s (1956) partial adjustment model. The results demonstrate that UK firms extensively rely on past dividend payments but partially on earnings to adjust their dividend decision-making. The analysis further implies that UK listed companies have a relatively clear and stable dividend policy and tend to pay cash dividends rather than stock dividends. A slight upward trend in the proportion of UK dividend payers is observed during the sample period. In addition, the research tests the determining factors that drive dividend policy using Fixed-effect regression model in a panel manner. The results highlight the importance of firms’ profitability position, and demonstrate that UK mangers prefer distributing cash dividends rather than stock dividends. Also, the author finds support for free cash flow and life-cycle hypotheses. Additionally, agency problems in United Kingdom are found to be quite series. However, the author does not observe significant impacts of firms’ leverage and liquidity level, investment opportunity or firm size on dividend payments.